1999
DOI: 10.1021/ja991506o
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Materials from Triblock Rodcoil Molecules Containing Phenylene Vinylene

Abstract: We report here on the synthesis and characterization of several triblock rodcoil molecules containing conformationally rigid and flexible sequences and luminescent chromophores based on phenylene vinylene. The molecules consist of blocks of oligostyrene, oligoisoprene, and a rigid rod block. The synthesis of the rod blocks required the preparation of new phenylene vinylene oligomers. On the basis of electron microscopy and X-ray diffraction experiments, these systems were found to self-organize into supramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 46 publications
6
88
0
Order By: Relevance
“…Other conjugated rod-coil block copolymers have been seen to assemble into ribbon-like fibrils [86] and non-spherical micelles [87]. Rod-coil triblocks containing oligo(phenylene vinylene) synthesized by Stupp and coworkers have been observed to self-assemble into mushroom shapes in solution [88][89][90], while poly(phenylquinoline-b-styrene) copolymers form hollow spheres when cast from specific solvent mixtures [91]. One of the main challenges to understanding and controlling order in these highly segregated, complex systems lies in obtaining and distinguishing equilibrium.…”
Section: Ordering Of Functional Block Copolymersmentioning
confidence: 99%
“…Other conjugated rod-coil block copolymers have been seen to assemble into ribbon-like fibrils [86] and non-spherical micelles [87]. Rod-coil triblocks containing oligo(phenylene vinylene) synthesized by Stupp and coworkers have been observed to self-assemble into mushroom shapes in solution [88][89][90], while poly(phenylquinoline-b-styrene) copolymers form hollow spheres when cast from specific solvent mixtures [91]. One of the main challenges to understanding and controlling order in these highly segregated, complex systems lies in obtaining and distinguishing equilibrium.…”
Section: Ordering Of Functional Block Copolymersmentioning
confidence: 99%
“…Most of the conjugated rod-coil copolymers have thus been obtained by convergent way, either by a simple condensation reaction between an end-functionalized coil polymer and the rod block [18][19][20][21][22] or by quenching a living coil polymer, synthesized by anionic polymerization, on an endfunctionalized conjugated oligomer. [23][24][25] This last approach leads to very-well controlled block copolymer since anionic living polymerization is an established technique to yield welldefined homopolymers and block copolymers. 26 The phase diagram of rod-coil block copolymers is by far less universal and less well-understood than that of the coilcoil block copolymers, and no systematic studies have been reported for rod-coil plus rod blends.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the strong anisotropy of rod-like blocks introduces large conformational asymmetry effects in rod-coil block copolymers which can have a considerable impact on the perturb self-assembled morphologies compared to coil-coil block copolymers [19]. The steadily increasing number of experimental and theoretical studies devoted to rod-coil block copolymers, has been triggered by the considerable advances in the synthetic 380 The European Physical Journal E routes followed to control their synthesis [5,[20][21][22][23][24][25][26][27]. In the present study we have taken advantage of the progress made on synthetic strategies to design rod-coil block copolymers, to synthesize two homologue series of rodcoil block copolymers having, respectively, i) the same π-conjugated rod block, ii) different coil polymers of variable molecular weight.…”
Section: Introductionmentioning
confidence: 99%